(3eSJbHd UfGOjb GdKQhI GdSjGOjI aj Xd GdHjFI GdeGdjI GdLOjOI s - (3HdbGSe(B, (3RGjQjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2020)
(3JfGhd GdLRA GdKGfj ef cJGH (B"(3UfGOjb GdKQhI GdSjGOjI hJMhdGJ GdfXGe GdeGdj GdOhdj(B" (3eSJbHd UfGOjb GdKQhI GdSjGOjI aj Xd GdHjFI GdeGdjI GdLOjOI , MjK bOe ef NdGd aUhd OQGSJg GdEWGQ GdbGfhfj GdOhdj ddGSJKeGQGJ GdCLfHjI hJWHjbGJg Ydi UfGOjb GdKQhI GdSjGOjI, hLZQGajI UfGOjb GdKQhI GdSjGOjI , HGdGVGaI Gdi UfGOjb Ohd GdNdjL GdYQHjI aj Xd GdHfjI GdeGdjI GdLOjOI (B.s
(3GdeQGLY U(B.307 s
Keywords: (3GdfXGe GdfbOj GdOhdjs